Academic procrastinators, strategic delayers and something betwixt and between: An interview study - Lindblom-Ylänne, Sari; Saariaho, Emmi; Inkinen, Mikko; Haarala-Muhonen, Anne; Hailikari, Telle (Frontline Learning Research, 2015)
The study explored university undergraduates’ dilatory behaviour, more precisely, procrastination and strategic delaying. Using qualitative interview data, we applied a theory-driven and person-oriented approach to test the theoretical model of Klingsieck (2013). The sample consisted of 28 Bachelor students whose study pace had been slow during their first university year. Three student profiles emerged. The first concerned strategic delay and was represented by motivated students with strong self-efficacy beliefs who had intentionally postponed their studying. The second consisted of students whose delaying was unnecessary in nature; these students had minor self-regulation problems but were still motivated to study. The third profile consisted of procrastinating students who lacked self-regulation skills and had weaker self-efficacy beliefs. The results indicate that dilatory behaviour can vary from strategic delay to dysfunctional procrastination, and that different factors are related to these various types of dilatory behaviour. This study adds to our theoretical understanding of academic procrastination by empirically testing a new theoretical model of procrastination. In addition, the study opens a new ‘methodological path’ to explore dilatory behaviour qualitative instead of following a strong tradition of using quantitative methods.